Extending the evaluation of social assistive robots with accessibility indicators. The AUSUS evaluation framework - Iglesias, Ana; García, Javier; García-Olaya, Angel; Fuenteja, Raquel; Fernández, Fernando; Romero-Garcés, Adrián; Marfil-Robles, Rebeca; Bandera-Rubio, Antonio Jesús; Lan Hing Ting, Karine; Voilmy, Dimitri; Dueñas, Álvaro; Suarez-Mejías, Cristina (IEEE, 2021)
The introduction of robots in the real world requires previous evaluation of the envisaged performance. Factors like usability, user experience, social acceptance or societal impact among others have been taken into account in evaluation frame- works defined during the last years. However, one of the most important factors that needs to be evaluated in any kind of interaction is whether all the users are able to work with the system with the same opportunities and easiness, and none of the current Human-Robot Interaction (HRI) evaluation frameworks include this factor yet. This paper proposes an extension of a popular HRI evaluation framework, including accessibility as a new evaluation factor. The proposed approach, named AUSUS, considers Accessibility, Usability, Social acceptance, User experience and Societal impact. This paper presents a use case of the framework, which is evaluated through a socially assistive robotic platform created to perform Comprehensive Geriatric Assessment: the CLARC - system. The details of the evaluation process in a hospital and a retirement home are reported and the main difficulties and recommendations of using AUSUS are discussed.
Keywords: Robótica; Asistencia social; Social assistive robotics; Accessibility